Twenty pageants later - Cooney, Caroline B. (New York : Bantam Books, 1991)
As the younger and plainer sister of a frequent beauty contest winner, fourteen-year-old Scottie-Ann has always had mixed feelings about such competitions especially when she finds herself a reluctant contestant in the Marsh Mid Princess Pageant.
"A Bantam starfire book"--Jacket.
5.7
5-8
5-8
Booklist
Kirkus Review
Keywords: Beauty contests -- Fiction; Self-perception -- Fiction; Interpersonal relations -- Fiction; Sisters -- Fiction; Schools -- Fiction; Contests -- Fiction; Beauty contests -- Fiction; Self-perception -- Fiction; Sisters -- Fiction; Human relations -- Fiction; Bildungsromane